Identifying the most notable events at the first stage of the solar cycle 25 - Jasim, Halla Abbas; Allawi, Habeeb (Edelweiss Applied Science and Technology, 2025)
This study documented 359 occurrences during the initial phase of solar cycle 25, spanning from December 2019 to April 2023. These events were the most powerful coronal mass ejections (CMEs). Out of the total of 359 events, four of them did not have any solar flares, whereas the remaining 355 events were linked to solar flares. This study involved the observation and analysis of solar events, which led to the identification of two significant coronal mass ejections that displayed robust shock waves. Both of these events displayed rapid linear velocities and significant angular widths. The coronal mass ejections were accompanied by solar flares that displayed exceptional intensity in the form of X-rays. The shock waves generated during these events provided valuable insights into the dynamics and transmission of coronal mass ejections. These findings enhance our comprehension of the impact of powerful events on the space environment by analyzing the attributes of shock waves.